The catcher in the rye - Salinger, J. D. (Jerome David), 1919-2010. (Boston : Little Brown, 1991)
An adolescent boy, knowing he is about to be dropped by his school, spends three days and nights in New York City.
Notable/Best Books (A.L.A.)
Wilson's Fiction
Wilson's Senior High School
Booklist, July 2008
Notable/Best Books (A.L.A.), March 2010
Wilson's Fiction, January 1996
Keywords: Adolescence -- Fiction; Caulfield, Holden (Fictitious character) -- Fiction; Adolescence -- Fiction; Caulfield, Holden (Fictional character) -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction